Circuit training method to improve strength endurance of cadets - Ignatov A.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the effectiveness of using the circuit training method in increasing the strength endurance of students at a military training center. Methods and structure of the study. To achieve this goal, a pedagogical experiment was conducted on the basis of the Educational Training Center at National Research Tomsk State University, in which 16 5th year students (male, age 22-23 years) enrolled in the military training program for personnel officers took part. From their number, experimental and control groups of eight people each were formed. The experimental group worked out according to a training plan, which contained exercises performed using the circuit training method. Research results and conclusions. The circuit training method can provide the greatest increase in results when used in exercises with a more pronounced strength component or external resistance factor - for example, in exercises with weights (squats with a barbell), since short series with a change in the muscle regions exposed to the impact provide better recovery between approaches bioenergetic systems responsible for the manifestation of strength abilities.